The effects of diallyl sulfide upon Porphyromonas gingivalis lipopolysaccharide stimulated proinflammatory cytokine expressions and nuclear factor‐kappa B activation in human gingival fibroblasts. (9th September 2014) - Fu, E.; Tsai, M.‐C.; Chin, Y.‐T.; Tu, H.‐P.; Fu, M. M.; Chiang, C.‐Y.; Chiu, H.‐C.
Abstract : Background and Objective: Diallyl sulfide (DAS), a flavor compound from garlic, has varied potential therapeutic activities. Periodontitis is a disease that develops because of host‐mediated inflammation to periodontal pathogens. In this study, the effects of DAS on the common proinflammatory cytokines and nuclear factor‐kappa B (NF‐κB) in human gingival fibroblasts (HGFs) being stimulated with lipopolysaccharide from Porphyromonas gingivalis, a potent periodontal pathogen, were evaluated. Material and Methods: Cytotoxicities of DAS and lipopolysaccharide on HGFs were measured with MTS assay. The mRNA and protein expressions of proinflammatory cytokines, including interleukin (IL)‐1β, IL‐6 and tumor necrosis factor (TNF)‐α, from the HGFs treated with lipopolysaccharide with and without DAS were examined with reverse transcription–polymerase chain reaction and immunocytochemistry, respectively. In addition, the activation and nuclear translocation of NF‐κB with and without DAS were compared. Results: DAS and lipopolysaccharide treatments within 3 mm and 10 μg/mL, respectively, did not affect the survival rate of HGFs. Lipopolysaccharide (1 μg/mL) significantly increased the mRNA expressions of IL‐1β, IL‐6 and TNF‐α; however, DAS (1 mm ) inhibited these expressions. The protein expressions of TNF‐α, IL‐1β, as well as the NF‐κB nuclear translocation were increased after lipopolysaccharide treatment, but decreased when there was a DAS pretreatment. Conclusion: DAS diminished P. gingivalis lipopolysaccharide‐stimulated cytokine expression and NF‐κB activation in HGFs; we therefore suggest DAS may be beneficial on periodontal inflammation.